New and interesting records of Plecoptera (Insecta) from Slovakia and several autecology notes - Žiak, Matej (Illiesia, 2014)
During the last five years several important discoveries of stoneflies from Slovakia were recorded, including Leuctra dalmoni Vincon & Murányi 2007, a recently described species and Rhabdiopteryx hamulata (Klapálek 1902), an uncommon Balkan species. We also recorded a curious find of the imago of the endangered species, Capnopsis schilleri (Rostock 1892), after 60 years.
Keywords: entomology; stoneflies; Leuctra; Plecoptera; Rhabdiopteryx; new species; Capnopsis